The Experience of Newly Diagnosed Women with Breast Cancer in Oman - Al-Marzouqi, Zalikha Khamis Darwish; Al-Suraihi, Nawal Said Salim; Al-Dhoani, Aida Said Bakeet (Journal of medical and pharmaceutical sciences, 2023)
Objective: It is well known that breast cancer have many impacts on women’s personal and professional life; therefore, this study sought to explore the experience of newly diagnosed women with breast cancer in Oman. This study would help to understand women’s knowledge, attitudes, views, beliefs with breast cancer and to understand the impact of breast cancer on their daily life. Methods: This study used a qualitative design, guided by a constructivist grounded theory approach. Semi-structured interviews with 20 women were conducted in the North Batinah Governorate of Oman. At the beginning of the data collection, purposive sampling relied on inclusion criteria was used. Then theoretical sampling was applied up to the point of data saturation. Results: The data from the interviews underwent constant comparative analysis and two main categories emerged from the data: “Knowing Breast Cancer” and “Being a Woman with Breast Cancer”. The data revealed that many women (60%) had poor understanding on breast cancer and they did not know the risk factors and warning signs of breast cancer. The data also revealed that majority of women (80%) knew the importance of conducting breast self-examination but they did not perform breast self-examination because of their busy life. Also, the data showed that clinical breast examination was conducted rarely within the healthcare institutions and it was limited for those women who had warning signs of breast cancer. The daily life of women diagnosed with breast cancer was within the framework of anxiety. Many women expressed their worrying feeling about their health condition and their personal and professional life. Conclusion: knowing the experience of women newly diagnosed with breast cancer from different aspects could help to provide the necessary educational and supportive services.
Keywords: Breast Cancer; Perception; Awareness; Attitudes; View and Impact